STUDI KUALITATIF KEHAMILAN TIDAK DIINGINKAN PADA REMAJA DI KELURAHAN SARIBUDOLOK KECAMATAN SILIMAKUTA KABUPATEN SIMALUNGUN - Lesterina Girsang (Jurnal Komunitas Kesehatan Masyarakat, 2020)
Unwilling pregnancy is the usual terminology used to give the term pregnancy is not desired by the woman in question. to describe the factors that affect unwilling pregnancy in adolescents in Saribudolok Village Silimakuta District Simalungun Regency. qualitative descriptive research with case study approach. The research informants were teenagers who had unwanted pregnancy with total number of informants 3 people and Triangulation Informant 6 people. The data retrieval technique is done by in-depth interview using interview guideline. The results showed that the cause of pregnancy is not desirable in adolescents are risky sexual behavior, less knowledge about reproductive health and sexuality, access to media information about pornography, parental attitudes toward adolescents Suggested to parents is more closer to the child and problems encountered and increase supervision of children who step on the age of adolescence.